Power converters for grid integration of solar energy - Tang, Li Zhu. (2011)
Renewable technologies have been growing in demand due to the recent shift to clean and green energy for its sustainability and environmental friendliness. Many research and developments have been carried out and several methods to efficiently control and harvest maximum power from these renewable sources are discovered. Solar energy is one of the favoured sources of renewable energy for its convenience and abundance in nature. Photovoltaic (PV) arrays have been used to harvest and convert solar energy into useful electricity for various applications. PV system, consisting of DC-DC buck/boost converter and DC-AC inverter, is often used to condition the DC output from PV array suitable for single- or three-phase load applications or even grid integration. This report would examine the several constituents of a PV system, and propose a new single-phase quasi Z-source inverter (qZSI) with power decoupling method to perform buck/boost operation and DC-AC inversion in a single-stage topology, while reducing the total harmonic distortion (THD) content in the output voltage and current with the decoupling effect. A simulation and hardware experiments have been done to show the efficacy of the proposed methods.